93.5k views
0 votes
Solve this equation. Enter your answer in the box. –4(x – 26) = –200\

2 Answers

0 votes

Answer:

76.

Explanation:

Simplifying

-4(x + -26) = -200

Reorder the terms:

-4(-26 + x) = -200

(-26 * -4 + x * -4) = -200

(104 + -4x) = -200

Solving

104 + -4x = -200

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-104' to each side of the equation.

104 + -104 + -4x = -200 + -104

Combine like terms: 104 + -104 = 0

0 + -4x = -200 + -104

-4x = -200 + -104

Combine like terms: -200 + -104 = -304

-4x = -304

Divide each side by '-4'.

x = 76

Simplifying

x = 76

User Majky
by
5.1k points
1 vote

Answer:

x is 76

Explanation:

im pretty sure, i just sloved it

User Gopesh
by
5.3k points